2019
DOI: 10.3897/mbmg.3.35060
|View full text |Cite
|
Sign up to set email alerts
|

DNA metabarcoding of Neotropical ichthyoplankton: Enabling high accuracy with lower cost

Abstract: Knowledge of ichthyoplankton dynamics is extremely important for conservation management as it can provide information about preferential spawning sites, reproductive period, migratory routes and recruitment success, which can be used to guide management and conservation efforts. However, identification of the eggs and larvae of Neotropical freshwater fish is a difficult task. DNA barcodes have emerged as an alternative and highly accurate approach for species identification, but DNA barcoding can be time-cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…DNA metabarcoding is a powerful tool for biodiversity assessment that has been widely used for several purposes and different taxonomic groups, including identification and quantification of neotropical ichthyoplankton 11 , 12 , stomach‐content analysis of a ray species 13 , and identification of wasp species using and comparing the Sanger and HTS methods 14 . Furthermore, environmental sampling (eDNA) has been successfully used for molecular identification of several vertebrate groups in temperate regions 15 17 , monitoring of endangered species such as freshwater fish in Australia and turtles in the United States 18 , 19 , and improved detection over traditional assessment methods for monitoring the invasive American bullfrog in France 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA metabarcoding is a powerful tool for biodiversity assessment that has been widely used for several purposes and different taxonomic groups, including identification and quantification of neotropical ichthyoplankton 11 , 12 , stomach‐content analysis of a ray species 13 , and identification of wasp species using and comparing the Sanger and HTS methods 14 . Furthermore, environmental sampling (eDNA) has been successfully used for molecular identification of several vertebrate groups in temperate regions 15 17 , monitoring of endangered species such as freshwater fish in Australia and turtles in the United States 18 , 19 , and improved detection over traditional assessment methods for monitoring the invasive American bullfrog in France 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Reid et al (2019) highlight the use of eDNA as one of the main conservation and management tools for dealing with the emerging threats for freshwater biodiversity. However, the potential of DNA metabarcoding to monitor vertebrate communities remains poorly explored in the Neotropical region, and few studies have been conducted to date 11,[21][22][23] .…”
mentioning
confidence: 99%
“…Whereas the CO1 marker has extensive sequence databases as well as a strong capability to discriminate between species, it also carries an increased risk of amplification bias due to the lack of conserved binding sites across a broad range of taxa (Deagle et al 2014). This can result in false negatives where taxa known to be present in a sample do not amplify (Collins et al 2019, Nobile et al 2019). Using more conserved priming sites, such as the 12S marker, may reduce taxa specific biases (Krehenwinkel et al 2017), although it has been argued that taxonomic resolution may be reduced due to lack of sequence variability within families (Thomsen et al 2016), and the completeness of reference databases also influences the resolution to species level (Miya et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While using the visual taxonomic approach, we identified one individual every 2–3 min on average. Furthermore, during recent years molecular barcoding methods have developed toward becoming both more time and cost efficient (Gleason and Burton 2012; Nobile et al 2019). In fact, the costs per individual analyzed in our study were similar to figures found in recent literature, estimated to be around $4 (Gleason and Burton 2012).…”
Section: Discussionmentioning
confidence: 99%